Exploratory Research on the Attitudes and Behaviors of Teachers from Chile in the Immigrant Student School Setting - Susan Valeria Sanhueza; Miguel Claudio Friz Carrillo; Segundo Quintriqueo Millán (Universidad Autónoma de Baja California, 2014)
The research assesses the opinion of elementary and high school students (n=339) on the instructional attitudes and behaviors of teachers at schools in Chile that enroll children and young foreigners. For this purpose, we used the Teacher Attitude and Behavior Towards Diversity Scale (Sanhueza, 2010), whose exploratory factor analysis groups 16 items on two factors, enabling the distinction between the teachers Attitude of Respect and their Fair Treatment towards students, including 12 items, and the Teachers Instructional Behavior, including four items. The results reveal that respondents perceived their teachers' attitudes and behaviors largely inclusive and they greatly value the respect, careful listening and support teachers show them when they have learning difficulties. Regarding gender, there were statistically significant differences in the responses on female students' favor, while comparing responses depending on educative stage, high school students find more inclusive attitudes and practices in their teachers.